Combined synthesis of aligned SiC nanofibers via electrospinning and carbothermal reduction. Issue 13 (September 2017) - Wang, Bing; Sun, Lian; Wu, Nan; Wang, Yingde
Abstract: Aligned nanofibers have extensive potential in the application of photoelectric devices and engineering due to their highly-ordered structure and large surface area. This paper describes a simple approach to the fabrication of well-aligned silicon carbide nanofibers (SiC NFs) by the carbothermal reduction of electrospun polyacrylonitrile (PAN) nanofibers and silicon powder. Microstructure characterization results showed that the obtained aligned SiC NFs had high purity and well-defined fiber shape. To keep the alignment of SiC NFs, the optimized spinning time is 5 min. The diameters of the resulted SiC NFs can be controlled from 149 to 491 nm. The obtained SiC NFs possess great potentials for application in electrical and optical devices, electrochemical sensors and tissue engineering.